Foreign investment in Indonesia The Legal Aspects under the New Indonesian Investment Law - Petra Bunawan (Faculty of Law, Maranatha Christian University, 2017)
Indonesia plays an important role in the ASEAN region as well as in the global community, therefore investment policy become one of the major concern to government. To meet and accomodate the business enviroment both domestic and overseas that need capital investment, thus to develop the economic growth and build a suistainable economic stability in the region as well as for the people of Indonesia, it is neccessary to stipulate the inevestment law that provide all the need . Therefore the government has replaced the old law with the new Investment Law, the law No 25 of 2007. The Law provides the basic principle of legal certainty, non discrimination and same treatment for investors both domestic and overseas. The principles of opennes, accountability, togetherness and the concept of repatriation support the friendly investment atmosphere in Indonesia. As well as the supportive fasilities and easy procedure for investors to invest and build business in Indonesia. One of important issues regarding to Investment law is to increase the direct investment, instead of indirect investment that its contribution has a difference impact to the real sectors and economic growth.The question is the law and supportive law accomodatively provides the need of investment enviroment, knowing the economic growth has been influenced by the era of globalization and in fact Indonesia has signed and ratified international agreement as well. This writing will give a slighty persfective according to Indonesian Investment law and other supportive law, both national and international . Keywords: Law, Investment, Government Regulation, Principles, international law